Catalyst-free activation of persulfate by visible light for water disinfection: Efficiency and mechanisms. (15th June 2019) - Wang, Wanjun; Wang, Hanna; Li, Guiying; An, Taicheng; Zhao, Huijun; Wong, Po Keung
Abstract: The development of cost-effective water disinfection methods is highly desired to address the problems caused by outbreak of harmful microorganisms. Sulfate radical (SO4 − )-based advanced oxidation technology has attracted increasing attention. However, various catalysts or UV irradiation are usually used to activate persulfate (PS), which is high-cost and the recovery of nano-sized catalysts is also challenging. This work demonstrates a new method of catalyst-free activation of persulfate by visible light (VL) for bacterial inactivation. The 6-log of E. coli cells can be inactivated within 40 min and 7-log of E. coli cells could be inactivated within 120 min by the VL/PS system. The major responsive wavelength is 420 nm, and no heat activation of PS is found during VL irradiation. A synergistic effect with synergy factor of 51.2% is found when combining the VL irradiation with heating at 50 °C. The acidic pH is benefit for the VL/PS-triggered bacterial inactivation, while bicarbonate inhibits the E. coli inactivation at the range of 0.1–20 mg/L. Mechanism study indicates the main reactive species are SO4 −, O2 − and OH, in which SO4 − plays the most important role. The bacterial inactivation process shows to begin from outer membrane to intracellular components. Subsequently, the antioxidant enzyme (i.e. SOD, CAT) is induced, followed by damaging to the genomic DNA leading to fatal death of the cells. In addition, the VL/PS system is also applicable for the inactivation of other pathogenic bacteria, including Staphylococcus aureus and Pseudomonas aeruginosa, showing universality for water disinfection applications. This work not only provides a new cost-effective disinfection method without a catalyst, but also sheds light on understanding the bacterial inactivation mechanism by SO4 − -based AOPs. Graphical abstract: Image 1 Highlights: VL was used to activate PS for bacterial inactivation without catalysts. Major responsive wavelength was found at 420 nm with no heat activation of PS. The .SO4 − was identified to play an important role in bacterial inactivation Intracellular antioxidant enzymes were induced, followed by damaging to DNA. The VL/PS system showed excellent inactivation towards two pathogenic bacteria.